Penerapan Media Papan Pintar Pancasila Pada Pembelajaran Pendidikan Pancasila Peserta Didik Kelas 1 SD N Jombor - Revina Rahmawati; Afisa Isnaini Irvana; Helga Putri Fatmawati; Isna Rahmawati (GLOBAL SCIENTS PUBLISHER, 2024)
This study aims to analyze Pancasila learning through the use of Pancasila smart board media in SD Negeri Jombor. With the use of Pancasila smart board learning media, it is hoped that students can increase their interest in learning about Pancasila symbols. This research method uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study showed that the use of smart board media was very helpful in the learning process of students. This research is expected to contribute to the learning process of Pancasila education in grade 1 of SD Negeri Jombor